Investigations on the mechanisms of ionic conductivity in PEO-PU/PAN semi-interpenetrating polymer network-salt complex polymer electrolytes: An impedance spectroscopy study - Basak P.; Manorama S.V.; Singh R.K.; Parkash O. (My University, 2025)
This paper is a first comprehensive study on the correlated ion transport mechanisms contributing to the overall conductivity behavior in a new class of poly(ethylene oxide)-polyurethane/polyacrylonitrile (PEO-PU/PAN) semi-interpenetrating polymer networks (semi-IPNs)-salt complex polymer electrolytes. A simultaneous investigation of the electrical response on PEO-PU/PAN/LiClO4 and PEO-PU/PAN/LiCF3SO3 semi-IPNs with varying EO/Li mole ratios (100, 60, 30, 20, 15, 10) has been carried out by impedance spectroscopy. Analysis of the complex plane and spectroscopic plots indicated the presence of two microscopic phases corresponding to the PEO-PU and PAN domains, which leads to space charge polarization in these systems. A suitably modified approach based on the universal power law (UPL) considering the independent contribution from the individual microphases of semi-IPNs facilitates a complete interpretation of the spectroscopic profiles for the real component of conductivity (o′(ω)). The o′ (ω) spectroscopic profiles were fitted with two power law equations, where the frequency region up to ∼300 kHz is the conductivity profile associated with the PAN phase and beyond this is the superimposed contribution of the PEO-PU phase. Simulated fits using the UPL equation revealed two relaxation times (τPEO-PU, τPAN) related to ionic hopping in the PEO-PU and PAN phases in addition to the conductivity relaxation time (τpeak) determined from the Debye peaks. The respective power law exponents (nPEO-PU ~∼ 0.5-0.8, nPAN ∼ 1.0-1.6) indicate that though cationic hopping in the softer PEO-PU phase is favored, anionic hopping in the PAN phase contributes significantly to the charge transport processes in these semi-IPNs. Correlation of the experimental results with the simulated fits enable us to distinguish the effects of semi-IPN composition, temperature, morphology, ion-ion, and ion-polymer interactions, which influence the microscopic molecular events, involved in the charge transport in these complex semi-IPN polymer electrolytes.